Rethinking sustainable biofuel marketing to titivate commercial interests - Edeseyi, M.; Kaita, A.; Harun, R.; Danquah, Michael; Acquah, C.; Sia, Joseph (Elsevier Science Ltd, 2015)
Even though considerable strides have been made in the development of effective technologies for the production of different biofuels in some commercial quantities, global consumer patronage in biofuel utilisation has been discouraging. This has triggered significant inquisitions and research into different key aspects of the biofuel supply chain some of which are; techno-economic innovations targeted at reducing production cost, product marketing and packaging, and sustainable resources for biomass generation. This paper seeks to investigate biofuel marketing modalities beyond the current scope of a majority public sector industry to aid the development and promotion of biofuels to commercial and public sectors. The need for marketing in the biofuel industry is explored to identify innovative strategies, trending capacities, and key success factors to revolutionise marketing schemes with the potential to predict future trends. Scholarly positions on effective strategies using well-known marketing paradigms are discussed to suit the need of the industry. A proposal for the application of a strategic marketing framework built on sustainability precept is put forward, concluding that sustainable marketing (green and social marketing) could be used concurrently and continuously to improve growth and development through increased sales and competitive scoping.